Primary tumor-derived exosomes facilitate metastasis by regulating adhesion of circulating tumor cells via SMAD3 in liver cancer. Issue 47 (22nd November 2018) - Fu, Qihan; Zhang, Qi; Lou, Yu; Yang, Jiaqi; Nie, Gang; Chen, Qi; Chen, Yiwen; Zhang, Jingying; Wang, Jianxin; Wei, Tao; Qin, Hao; Dang, Xiaowei; et al.
Abstract Hepatocellular carcinoma (HCC) is a fatal disease and patients with HCC frequently die from metastasis. The mechanisms of HCC metastasis are not completely understood. In the present study, in vitro and in vivo data showed that HCC cells promoted cancer cell proliferation and lung metastases formation in a paracrinal/endocrinal way. We found that HCC-derived exosomes mediated this phenomenon and observed enhanced cell adhesion in the presence of these malignant exosomes. We further identified that reactive oxygen species (ROS) regulated the adhesive molecules. Intriguingly, attached HCC cells released exosomes containing both SMAD Family Member 3 (SMAD3) protein and mRNA, which were delivered to detached HCC cells and facilitated their adhesion. These exosomes induced enhanced SMAD3 signaling in the recipient HCC cells and increased their adhesive ability. In addition, we showed that SMAD3-abundant exosomes existed in the peripheral blood of patients with HCC, and their levels correlated with disease stage and the SMAD3 expression of primary tumors. Our study suggested a possible mechanism by which primary HCC supported metastases formation and revealed the role of SMAD3 in the exosomes-mediated crosstalk between primary and circulating HCC cells.